Anti-Neural Autoantibodies Associated with Major Depressive and Bipolar Disorders: Characterization of Psychopathology and Literature Review - Hansen, Niels; Teegen, Bianca; Fitzner, Dirk; Wiltfang, Jens (Journal of Psychology and Psychotherapy Research, 2024)
Background; Neural autoantibodies in depression are rarely reported, and their prevalence in depression is unknown. Our study was therefore dedicated to analyzing the frequency of neural autoantibodies in a cohort of patients presenting mood disorders. In addition, the study served to describe the clinical psychopathology of the patients with depressive disorders and neural autoantibodies. Methods; We retrospectively examined a cohort of 41 patients with major depressive disorder and bipolar affective disorder. Patient files were evaluated for clinical data, psychopathological assessment, as well as magnetic resonance imaging (MRI), electroencephalography (EEG), cerebrospinal fluid analysis findings and serum and/or cerebrospinal fluid (CSF) neural autoantibodies. Results; Our study revealed neural autoantibodies in of 6 of 41 (14%) of patients with mood disorders suspicious for an underlying organic cause. CSF autoantibodies were verified in 3 of 41 (7%) patients with mood disorders. No differences between antibody-positive and -negative mood disorder patients were identified regarding psychiatric syndromes or CSF, EEG, MRI and psychopathological parameters. However, mood-disorder patients with autoantibodies revealed less loss of drive than those mood disorder patients without autoantibodies. Conclusions; Our findings indicate that a minority of mood disorders might be associated with neural autoantibodies. The proof of CSF autoantibodies in three of six autoantibody-positive patients suggests highly likely paraneoplastic or autoantibody-mediated autoimmunity. Our study’s novelty is the in-depth phenotyping of autoantibody-positive depressed patients via two different psychometric scoring systems. More research is required to confirm these preliminary results in larger cohorts with more homogeneous patient groups.